Theories and Methods Involved in the Interpretation and Assessment of the Financial Security of the State in the Context of Socio-Economic Transformation - I. ZAICHKO (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2021)
Theoretical and methodological tools for determining and assessing financial security have been deepened. An analysis of the publications of Ukrainian scholars on approaches to the interpretation of the concept of “financial security”, including the definition of components of financial security, which shows that most often it is allocated to budget security. A matrix of approaches to determining the components of financial security. The essence and nature of budget security are determined, it is shown that budget security is the main component of financial security, which indicates the importance of budget policy in the system of financial security of the state. The author’s definition of financial security of the state as a state of stability and stable protection against threats in the budget sphere, which is characterized by ensuring the solvency of the state and a high level of budget, debt, banking, currency, monetary security and is achieved through effective fiscal policy. Based on the Guidelines for calculating the level of economic security of Ukraine of the Ministry of Economic Development and Trade of Ukraine from 2013, 6 indicators (sub-indices) of economic security of Ukraine for 2016–2018 were calculated (banking security, security of non-banking financial sector, debt security, currency security, monetary credit security and budget security), as well as an integrated indicator of financial security of Ukraine. The results of calculations show that the financial security of Ukraine in 2016–2018 was at a dangerous level, which confirms the need to form and implement a set of policy measures to support it.